Therapeutic Effect of Ecklonia cava Extract in Letrozole-Induced Polycystic Ovary Syndrome Rats - Yang, Hyun; Lee, Seung Yeon; Lee, Sang R.; Pyun, Bo-Jeong; Kim, Hye Jin; Lee, Young Ho; Kwon, Sun Woo; Suh, Dong Ho; Lee, Choong Hwan; Hong, Eui-Ju; Lee, Hye Won (Frontiers in Pharmacology, 2018)
Polycystic ovary syndrome (PCOS) is an endocrinal disorder that afflicts mainly women of childbearing age. The symptoms of PCOS are irregular menstrual cycles, weight gain, subfertility and infertility. However, because the etiology is unclear, management and treatment methods for PCOS are not well established. Recently, natural substances have been used for PCOS therapy. Ecklonia cava (E. cava) is a well-known natural substance that attenuates the effects of inflammation, allergies and cancer. In this study, we investigated the effects of E. cava extract in rats with PCOS. When rats with letrozole-induced PCOS were exposed to the E. cava extract, the regular estrus cycle was restored, similar to that in placebo rats. Hormone levels, including the levels of testosterone, estrogen, luteinizing hormone (LH), follicle stimulating hormone (FSH) and anti-Müllerian hormone (AMH), were restored to their normal states. Histological analysis revealed that the polycystic ovary symptoms were significantly decreased in the E. cava-treated rats and were comparable to those of normal ovaries. At the transcriptional and translational levels, Cyp19a1, Ar, Esr1, Esr2 and aromatase levels were markedly increased in the E. cava-treated rats with PCOS compared with the rats with letrozole-induced PCOS. These results suggest that the E. cava extract inhibits the symptoms of PCOS by restoring imbalanced hormonal levels and irregular ovarian cycles in letrozole-induced female rats.